Magnetoelectric coupling at room temperature in LaTiO3/SrTiO3 heterojunctions - Simoes, A. Z. [UNESP]; Ortega, P. P. [UNESP]; Ramirez, M. A. [UNESP]; Moreno, H. [UNESP]; Aldao, C. M.; Ponce, M. A.; Moura, F. (Elsevier, 2023)
This work focuses on LaTiO3 (LTO) thin films synthesized by the polymeric precursor method and deposited onto SrTiO3 (STO) substrates via spin coating. The results show interesting coexisting ferromagnetic (Mr≈2.85 emu/g) - ferroelectric (Pr≈18.5 μC/cm2) responses at room temperature. Magnetoelectric coupling can be observed under DC bias magnetic field (14 V/cm.Oe), and its dielectric constant is affected by the coupling between magnetic and electric dipoles at room temperature as well as oxygen octahedra distortion along direction a. Little film-substrate mismatch significantly influences the system dielectric properties. Our results suggest the possibility to induce ferromagnetic/ferroelectric phases in the LTO/STO heterojunctions using an electric/magnetic field, respectively, due to the magnetoelectric coupling. This study also helps comprehend oxygen vacancy dynamics when applying a tensile strain or an external electric field, which is fundamental for actuators, switches, magnetic field sensors, and new types of electronic memory devices.
Keywords: Chemical synthesis; Mott insulator; Multiferroic; Thin films